DEVELOPING A TASK-BASED LANGUAGE LEARNING (TBLL) MODEL IN THE TEACHING OF WRITING SKILLS FOR STUDENTS OF ENGLISH LANGUAGE PROGRAM - Ilham, - (2021)
The task-based learning model involves students to process features of tasks as the basic unit for attaining language skills so that they can use it in the real world. This model pays an attention to utilize various tasks in learning activities to acquire writing skills. This research is aimed to (1) identify the needs of students of the English department at two private universities in the teaching of writing skills as the tasks assessed using Task-Based Language Learning (TBLL) (2) develop a task-based language learning model in the teaching of writing skills for students of English Language Program at higher education (3) explore the degree to which Task-Based Language Learning (TBLL) is able to help students enhance their writing skill. This study was research and development applying the steps development of Design-Based Research procedure proposed by Bannan (2009). The steps include informed exploration, enactment, and evaluation. The TBLL model consisted of five stages which are the steps of introduction, habit formation, construction, reflection, and presentation. In the process of implementing the TBLL model, this study employed a quasi-experimental study. The stages of the TBLL model were completed in sixteen meetings. The effectiveness of the TBLL model was measured based on the students' responses, lecturers' opinions, and writing scores. This research was conducted in two private universities in Mataram, West Nusa Tenggara. The subject of the study were 66 fifth-year students of the English Department of the two private universities in Mataram in the academic year 2019/2020. The data were collected through a questionnaire, semi-structured interview, observation sheet, and writing test. The data were analyzed by applying quantitatively and qualitatively using the Saphiro Wilk test, one-way ANOVA, and analysis of covariance at the significance level .05. The research findings were as follows: (1) students of the English department at two universities need to learn text types in their writing class, mastering vocabulary, punctuation in English and construct sentences into a paragraph, (2) the visualized model of task-based language learning steps was modified into habit formation, reflection and presentation, the developed model is conceptually well-developed according to the expert validation. The validation of the model viewed from aspects of supporting theories, practicality, and elaboration based on experts' and practitioners' assessment was found to be in the very good category. (3) The ANCOVA computation confirms that the developed model is significantly effective in enhancing the students' academic writing achievement in terms of content organization,vocabulary, language use, and mechanic.